2017
DOI: 10.1016/j.jtumed.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards epilepsy in Saudi families

Abstract: Objectives Epilepsy is one of the most common paediatric neurological disorders. Lack of awareness regarding epilepsy among the general population influences the lives of epileptic children. Misconceptions and misinformation about epilepsy in children should be identified and corrected. The aim of this study was to assess the knowledge and attitudes towards epilepsy in families of epileptic children and families of normal children in Almadinah Almunawwarah, KSA. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…On the other hand, there was a positive attitude towards epilepsy among 88% of Saudi families regarding the good academic performance and intelligence of epileptic (13) . Also, in Riyadh, the same results were shown about the successfulness and achievement of epileptic child (16) .…”
Section: (16-18)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there was a positive attitude towards epilepsy among 88% of Saudi families regarding the good academic performance and intelligence of epileptic (13) . Also, in Riyadh, the same results were shown about the successfulness and achievement of epileptic child (16) .…”
Section: (16-18)mentioning
confidence: 99%
“…The tool used in this study was a pre tested questionnaire that was based on other studies conducted in different parts of KSA among Saudi parents (13,14) . The questionnaire included the demographics of included subjects and the source of their information, items regarding the knowledge about epilepsy, questions about the attitude and items about practice pattern.…”
Section: Study Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussion. Many regional studies have reported the perceptions and attitude of the general population towards epilepsy 10,12 and its prevalence which is known to be roughly 6.54 among every 1000 Saudi individuals. 13 The results revealed the prevalence to be 2.67%, which is significantly lower than some studies 14 but higher than the others.…”
Section: Ethical Considerations the Ethical Approval Was Obtained Frmentioning
confidence: 99%
“…Epilepsy is defined as recurrent unprovoked seizures generated from excessive and abnormal cortical neuronal activity in the brain. An episode of epilepsy is characterized by a convulsive or non-convulsive seizure [ 4 , 5 ]. In pediatric population, it is very often associated with cognitive, behavioral and psychiatric comorbidities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%